Analysis of Diversity & Inclusion Implementation, Online Training, and Adaptive Leadership on Employee Engagement in Digital Startups in West Java - Farida Arinie Soelistianto; Harrij Mukti Khristiana; Salwa Aulia Novitasari (West Science Interdisciplinary Studies, 2025)
This study explores the impact of Diversity & Inclusion Implementation, Online Training, and Adaptive Leadership on Employee Engagement in digital startups located in West Java. The research employs a quantitative approach with a sample size of 170 employees, utilizing a Likert scale (1-5) for data collection and data analysis performed through Structural Equation Modeling (SEM-PLS 3). The findings reveal that all three factors significantly influence employee engagement, with Adaptive Leadership having the strongest impact, followed by Diversity & Inclusion Implementation and Online Training. The study highlights the importance of adaptive leadership in fostering employee motivation and commitment, as well as the role of inclusive practices and continuous learning opportunities in enhancing employee engagement. The implications of these findings are discussed, with recommendations for digital startups to focus on leadership development, diversity initiatives, and training programs to improve employee engagement and organizational performance.